Oncogenic Activation of YAP Signaling Sensitizes Ferroptosis of Hepatocellular Carcinoma via ALOXE3-Mediated Lipid Peroxidation Accumulation - Qin, Yifei; Pei, Zhuo; Feng, Zhuan; Lin, Peng; Wang, Shijie; Li, Yong; Huo, Fei; Wang, Quancheng; Wang, Zhiping; Chen, Zhi-Nan; Wu, Jiao; Wang, Yi-Fei (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis, a form of programmed cell death process driven by iron-dependent lipid peroxidation, plays an important role in tumor suppression. Although previous study showed that intracellular Merlin-Hippo signaling suppresses ferroptosis of epithelial tumor cells through the inactivation of YAP signaling, it remains elusive if the proto-oncogenic transcriptional co-activator YAP could serve as a potential biomarker to predict cancer cell response to ferroptosis-inducing therapies. In this study, we show that both total YAP staining and nuclear YAP staining were more prevalent in HCC tissues than in nontumorous regions. Compared to low-density HCC cells, high-density cells showed decreased nuclear localization of YAP and conferred significant resistance to ferroptosis. Oncogenic activation of YAP signaling by overexpression of YAP(S127A) mutant sensitized ferroptosis of HCC cells cultured in confluent density or in the 3D tumor spheroid model. Furthermore, we validated the lipoxygenase ALOXE3 as a YAP-TEAD target gene that contributed to YAP-promoted ferroptosis. Overexpression of ALOXE3 effectively increased the vulnerability of HCC cells to ferroptotic cell death. In an orthotopic mouse model of HCC, genetic activation of YAP rendered HCC cells more susceptible to ferroptosis. Finally, an overall survival assay further revealed that both a high expression of YAP and a low expression of GPX4 were correlated with increased survival of HCC patients with sorafenib treatment, which had been proven to be an inducer for ferroptosis by inhibition of the xc- amino acid antiporter. Together, this study unveils the critical role of intracellular YAP signaling in dictating ferroptotic cell death; it also suggests that pathogenic alterations of YAP signaling can serve as biomarkers to predict cancer cell responsiveness to future ferroptosis-inducing therapies.